Cross-link degree dependence of electronic, water uptakes and thermal-mechanical properties of epoxy resin polymers: molecular simulations - Li, Shuang Cui (2023)
Epoxy resin (EP) is a widely used polymer matrix. A deep understanding of the structure/property relationship of EP at the molecular level is critical to realizing the materials’ full potential. Here, molecular simulations are used to calculate and compare the electronic, water uptakes and thermal-mechanical properties of EP dependent on different cross-link degrees, bisphenol A diglygde ether (DGEBA) cross-linked with methyl-tetrahydro phthalic anhydride (MTHPA), revealing these inter-relationships. The results show that they have the same energetic spectrum character of electronic states, which is determined by compositions and bonding configurations of chemical groups in EP polymers, only with the different magnitudes of the density of states which are proportional to the number of cross-link points or curing agents and monomers. Furthermore, the van der Waals forces, not the cross-link chemical bonds, dominate the molecular chain interactions and motions in EP polymers below the glass transition temperature, while cross-link structure determines the configuration of the aggregated molecular chains and thermal properties of EP polymers above the glass transition temperature. Meanwhile, the hydrostatic mechanical modulus of EP material is primarily derived from cross-link structure even below the glass transition temperature. These results lay the foundation for designing and manufacturing customized EP with desirable electric and thermal-mechanical properties.